2015
DOI: 10.1097/iae.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness and Volume in a Healthy Pediatric Population and Its Relationship With Age, Axial Length, Ametropia, and Sex

Abstract: Healthy pediatric subjects exhibit choroidal differences in refractive error and AL. In the study population, CT and volume show an increase with age after adjusting for AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
20
1
1
Order By: Relevance
“…To the best of our knowledge, we are the first to demonstrate that the recovery of amblyopia had no significant effect on choroidal thickness. In our study, as in previous studies, choroidal thickness was significantly correlated with axial length. Therefore, it can be stated that the thickening of the choroid that has been found previously in the eyes with hyperopic anisometropic amblyopia may be an artefact of the correlation between choroidal thickness and hyperopia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, we are the first to demonstrate that the recovery of amblyopia had no significant effect on choroidal thickness. In our study, as in previous studies, choroidal thickness was significantly correlated with axial length. Therefore, it can be stated that the thickening of the choroid that has been found previously in the eyes with hyperopic anisometropic amblyopia may be an artefact of the correlation between choroidal thickness and hyperopia.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Mori and colleagues speculated that choroidal accommodation might be inhibited with the diminutive visual feedback in the amblyopic eye; however, in all of these studies, amblyopic eyes were more hyperopic than the control eyes and it was not clear whether this choroidal thickening resulted from amblyopia or hyperopia. It has been demonstrated that there is a positive correlation between SE and choroidal thickness and a negative correlation between axial length and choroidal thickness . To the best of our knowledge, we are the first to demonstrate that the recovery of amblyopia had no significant effect on choroidal thickness.…”
Section: Discussionmentioning
confidence: 58%
“…Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlementioning
confidence: 54%
“…[4][5][6][7][8] In addition, it is known that ChT is affected by various factors such as blood pressure, age, gender, time of the day, refractive status, axial length, and forced hyperopic or myopic defocus. 2,[9][10][11] Further, a recent experimental study showed that anti-muscarinic agents could affect ChT. 12 Therefore, in the present study, we aimed to investigate the effects of tropicamide and cyclopentolate, which are two anti-muscarinic agents commonly used in the ophthalmologic practice, on subfoveal ChT measured by EDI OCT in healthy adults.…”
Section: Introductionmentioning
confidence: 99%